Achieving Universal Primary Education: Mid-day Meal Programme in Residential Schools for the Scheduled Tribes in Chhattisgarh - Panda, B. K. (JOURNAL OF INDIAN EDUCATION, 2010)
School feeding programme is crucial for children who are attending schools in general and the hungry and malnourished children in particular. Timely provision of food packages in the schools in a variety of forms to the children in United States of America, Jamaica, Malawi, Burkina Faso, Brazil, Pakistan, Nepal and Bangladesh have taken care of under nourished children leading to good health that contributed substantially to the learning in schools. Studies have proved that food provisions have improved attendance, reduced drop outs and in some countries it proved to improve their learning abilities and arithmetic skills. India is no exception, where good results are being achieved due to the National Mid Day Meal Programme. The school feeding programme is not new to the Indian context and especially the residential schools functioning in the Tribal Areas of the country. These residential schools had this provision from a long time, in fact these schools provided the food for the entire day to the Scheduled Tribe Children to ensure proper health and overcome malnutrition among these children. This article has made an attempt to focus on various issues relating to the package of mid-day meal programme and its positive affects/impact in achieving universal primary education especially in the residential schools of Chhattisgarh.